FAKTOR – FAKTOR YANG MEMPENGARUHI PERMINTAAN TANAMAN ANGGREK (Orchidaceae) DI KOTA MEDAN - Khairunnisa Rangkuti (Universitas Medan Area, 2018)
The purpose of this study was to determine the effect of prices, consumer tastes, income and location / place to Requests Orchid Plant in the city of Medan, and to know the Demand Elasticity of orchids in the city of Medan. The data collected from the data Primary and Secondary Data. Based on the results of testing statistical analysis obtained by value Multiple R of 86.6%. The value of F table at the level of 0.05 is thus calculated F 2,76 = 18.801> F table = 2.76 at 95% confidence level. Furthermore, in testing T test, to see the effect of demand factors partially on the request of orchids, the value of the T-table 2.045 with a confidence level of 86.6%. X2, X3 and X4 real impact While real variables X1 No Effect on Demand (Y). Analysing the value of Elasticity, Elastic Retrieved much as 3.395> 1. Demand level of sensitivity to the independent variable (tastes, income, and location) of 3.395.